Odpowiedź:
Szczegółowe wyjaśnienie:
Do wszystkich podanych przykładów będzie zastosowany wzór skróconego mnożenia a² – b² = (a – b)∙(a + b)
x²/(x² - 9) • (x - 3)/x = x/(x² - 9) • (x - 3) =
= [x/(x - 3)(x + 3)] • (x - 3) = x/(x + 3)
2x/(x + 6) • (x² - 36)/x² = 2/(x + 6) • [(x² - 36)/x] =
= 2/(x + 6) • [(x - 6)(x + 6)/x] =
= 2 • [(x - 6)/x] = 2(x - 6)/x
(4x² - 1)/4 • 6/(2x - 1) = [(4x² - 1)/2] • 3/(2x - 1) =
= [(2x - 1)(2x + 1)/2] • 3/(2x - 1) =
= [(2x + 1)/2] • 3 = 3(2x + 1)/2
(3x+2)/3 • 12/(9x² - 4) = (3x+2) • [4/(9x² - 4)] =
= (3x+2) • [4/(3x - 2)(3x + 2)] =
= [4/(3x - 2)] = 4/(3x - 2)